Mentoring as a strategy for recognizing and attending to school violence - Niño Zúñiga, Mayra Guadalupe; Escalante Rodríguez, Juan de Dios (Trabajo Social UNAM, 2016)
This article points out the importance of mentoring, be it individual or group, as a strategy for recognizing and addressing school violence and thus promoting academic performance at the National School of Social work or the UNAM, noting the need for intervention in the diagnosis and support for solving learning problems, recognizing the need for interdisciplinary work on a the complex issue such as violence. We are not interested in discussing the concept of mentoring but rather in working with concepts which make mentoring easier. The aim of this study is to share the attempt Mentoring as a strategy for recognizing and attending to school violence Mayra Guadalupe Niño Zuñiga Juan de Dios Escalante Rodríguez Nowadays school violence is a complex matter calling for the attention of various disciplines and specialists from the academic and research community since it has over the past decades become an ever more evident global problem to describe the participation of teachers and students in the field of mentoring in detecting situations of school violence. This proposal is the result of analysis and reflection on the relationship between Educational Guidance, understood in its broadest sense, and mentoring, as one of the functions of teachers in their day-to-day work.